SHRM-BNA SURVEY PREVIEW. (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Handwritten; Bulletin for Management entitled “SHRM (Society for Human Resource Managements) and BNA (Bureau of National Affairs) Survey Preview.” Investigates smoking bans in the workplace via survey. Finds that 34% of workplaces have smoking policies, smoking rules have extended beyond the workplace in many instances, non smokers morale has improved, and workplaces without policies are planning to incorporate them in the future. Adds handwritten page with propositions to combat this policy.